2019
DOI: 10.1186/s12917-019-1881-1
|View full text |Cite
|
Sign up to set email alerts
|

Center of pressure limb path differences for the detection of lameness in dogs: a preliminary study

Abstract: Background The limb center of pressure (COP) path measures and quantifies the load distribution within a limb in a still or moving subject. Under this premise, the aim of this study was to test whether data derived from this parameter could detect the differences between sound and lame limbs in unilaterally lame dogs with elbow dysplasia. To accomplish this purpose, ten unilaterally lame dogs of similar conformation were walked over a pressure platform. Next, the COP path, in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 26 publications
(39 reference statements)
3
46
0
Order By: Relevance
“…The study by Lopez et al [16] used dynamic measurements to investigate COP limb path differences of dogs with osteoarthritis due to elbow dysplasia. Despite the similar approach, a comparison with our results is difficult due to different investigated parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Lopez et al [16] used dynamic measurements to investigate COP limb path differences of dogs with osteoarthritis due to elbow dysplasia. Despite the similar approach, a comparison with our results is difficult due to different investigated parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mentioned study showed that differences in COP parameters between sound and lame limbs exist in diseased animals, which is in accordance with our findings. Although in the study of Lopez et al [16] promising parameters were already used to investigate the COP in the paw of the walking dog, in this paper, we partially used different parameters. Further studies should investigate which parameters (or possible combinations thereof) are best suited to describe compensatory changes of the COP caused by osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSW system has been used in both healthy [36,25] and lame [16,17,37] dogs and the reference data have been obtained. Using especially PVF data, the data of the dogs with orthopedic problems have been compared.…”
Section: Discussionmentioning
confidence: 99%